Radiation, photosynthesis, yield, and fruit quality of ’Royal Gala’ apples under hail protection nets - Amarante, Cassandro Vidal Talamini do; Steffens, Cristiano André; Mota, Clenilso Sehnen; Santos, Henrique Pessoa dos (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to assess the amount and quality of the light supplied to plants, and the resulting impacts on photosynthesis, yield, and fruit quality of 'Royal Gala' apple trees uncovered or covered with white and black hail protection nets. The black net caused a higher reduction (24.8%) of photosynthetic photon flux density, accumulated over the plant canopy during the day, than the white net (21.2%). The canopy internal portion of plants covered by black net received lower levels of ultraviolet, blue, green, red, and far red radiation, and light with a lower red:far red ratio, in comparison to uncovered plants; these ligth changes increased chlorophyll content and specific area of the leaves, and reduced the potential photosynthesis, the weight of fruits per cm2 of trunk cross section area, and the share of blush area in the fruit. White and black hail protection nets reduced the incidence of sunburn, but had no effect on russeting severity and number of seeds per fruit.